Longest terrestrial migrations and movements around the world - Joly, Kyle; Gurarie, Eliezer; Sorum, Mathew S.; Kaczensky, Petra; Cameron, Matthew D.; Jakes, Andrew F.; Borg, Bridget L.; Nandintsetseg, Dejid; Hopcraft, J. Grant C.; Buuveibaatar, Bayarbaatar; Jones, Paul F.; Mueller, Thomas; et al. (Scientific reports, 2019)
Long-distance terrestrial migrations are imperiled globally. We determined both round-trip migration distances (straight-line measurements between migratory end points) and total annual movement (sum of the distances between successive relocations over a year) for a suite of large mammals that had potential for long-distance movements to test which species displayed the longest of both. We found that caribou likely do exhibit the longest terrestrial migrations on the planet, but, over the course of a year, gray wolves move the most. Our results were consistent with the trophic-level based hypothesis that predators would move more than their prey. Herbivores in low productivity environments moved more than herbivores in more productive habitats. We also found that larger members of the same guild moved less than smaller members, supporting the ‘gastro-centric’ hypothesis. A better understanding of migration and movements of large mammals should aid in their conservation by helping delineate conservation area boundaries and determine priority corridors for protection to preserve connectivity. The magnitude of the migrations and movements we documented should also provide guidance on the scale of conservation efforts required and assist conservation planning across agency and even national boundaries.